2023
DOI: 10.1088/2058-6272/acd83c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on the uniformity of nanosecond pulsed dielectric barrier discharge influenced by pulse parameters

Abstract: Nanosecond (ns) pulsed dielectric barrier discharge (DBD) is considered as a promising method to produce controllable large-volume and high activity low-temperature plasma at atmospheric pressure, which makes it suitable for wide applications. In this paper, the ns pulse power supply is used to excite Ar DBD and the influences of the pulse parameters (voltage amplitude, pulse width, pulse rise and fall times) on the DBD uniformity are investigated. The gas gap voltage (Ug) and conduct current (Ig) are separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Considering the complicated discharge characteristics of large-scale DBD under different experimental conditions, it is necessary to extract the discharge characteristic parameters and establish the correction between multi-dimensional discharge parameters and plasma characteristics [20,21]. Machine learning is an effective method that can independently learn the structure and internal patterns of input sample data, which has been applied in deep-going analysis of plasma properties [22], such as surface micro-discharge identification [23], trace gas detection [24], carbon dioxide methane reforming [25], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complicated discharge characteristics of large-scale DBD under different experimental conditions, it is necessary to extract the discharge characteristic parameters and establish the correction between multi-dimensional discharge parameters and plasma characteristics [20,21]. Machine learning is an effective method that can independently learn the structure and internal patterns of input sample data, which has been applied in deep-going analysis of plasma properties [22], such as surface micro-discharge identification [23], trace gas detection [24], carbon dioxide methane reforming [25], etc.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have demonstrated that the dielectric materials are of great importance for the discharge characteristics and the application effects of DBDs. However, the functions of the dielectric materials participating in the DBD processes are more complex, especially in DBD pulsed by nanosecond (ns) pulses, which involve the fast spatiotemporal evolution of the space electric field, the seed electron production, the charge accumulation and decay on dielectric barrier layer surface [30][31][32]. The previous results are mostly observed in specific conditions and there is lack of the comprehensive studies on the mechanisms of the dielectric materials on DBD processes.…”
Section: Introductionmentioning
confidence: 99%